Ethereal packet sniffing - Orebaugh, Angela; Morris, Greg.; Warnicke, Ed.; Ramirez, Gilbert; Syngress Media, Inc. (Rockland, Mass. : Syngress ; Oxford : Elsevier Science, 2004)
This book provides system administrators with all of the information as well as software they need to run Ethereal Protocol Analyzer on their networks. There are currently no other books published on Ethereal, so this book will begin with chapters covering the installation and configuration of Ethereal. From there the book quickly moves into more advanced topics such as optimizing Ethereal's performance and analyzing data output by Ethereal. Ethereal is an extremely powerful and complex product, capable of analyzing over 350 different network protocols. As such, this book also provides readers with an overview of the most common network protocols used, as well as analysis of Ethereal reports on the various protocols. The last part of the book provides readers with advanced information on using reports generated by Ethereal to both fix security holes and optimize network performance. Provides insider information on how to optimize performance of Ethereal on enterprise networks. Book comes with a CD containing Ethereal, Tethereal, Nessus, Snort, ACID, Barnyard, and more! Includes coverage of popular command-line version, Tethereal.
One CD-ROM in pocket attached to inside back cover.
Disc contents: Installation, reference, and packet capture files; Ethereal 0.10.0 installation files for Windows, Red Hat Linus 9.0, and Solaris 9; Ethereal source code; Ethereal display filter reference; packet capture examples.
Includes index.
Keywords: Computer networks -- Security measures; Computer network protocols; Electronic books